Influence of Air Quality on Pro-environmental Behavior of Chinese Residents: From the Perspective of Spatial Distance - Sheng, Guanghua; Dai, Jiatong; Pan, Hong (Frontiers in Psychology, 2020)
Although environmental issues have attracted public attention, there are still many people unwilling to make behavioral changes to solve the problem, which makes promoting pro-environmental behavior become an interesting research topic. This study discusses the influence of air quality on the pro-environmental behavior of Chinese residents from the perspective of spatial distance, providing a theoretical basis and practical application for improving pro-environmental behavior. Through three experiments, this study reveals that air pollution within the local spatial distance could make residents more willing to conduct pro-environmental behavior. In addition, we also find that air pollution within local spatial distance would stimulate residents’ environmental affection and promote them to conduct pro-environmental behavior. That is, environmental affection plays a mediating role in the interactive effect of air quality and spatial distance on pro-environmental behavior.